Atonement and forgiveness : a new model for Black reparations - Brooks, Roy L. (Roy Lavon), 1950- (University of California Press, 2004)
Roy Brooks reframes one of the most important, controversial & misunderstood issues of modern times in this reassessment of the debate on black reparation. He shifts the focus from the backward-looking question of compensation for victims to a more forward-looking opportunity for racial reconciliation.